Effect of temperature, relative humidity and botanicals on Alternaria and Asp ergillus fruit rots in ber fruits. (Indian Journal of Arid Horticulture, 2025)
cThe disease severity due to Altemaria altemata and Aspergi/11.r niger was highest at 25 and 30 'C, respectively. The temperature and relative humidity influenced the development of fruit rots due to A. a/ternata and A. niger symptoms ranges tested. Severity of Alternaria fruit rot was maximum at 25 •c and I 00 per cent relative humidity while severity of Aspergillus fruit rot was maximum at 30 'C and 100 per cent relative humidity. Neem oil and groundnut oil used as pre inoculation treatment effectively reduced the severity of Altemaria fruit rot. In case of Aspergll/us ·fruit rot neem oil and castor oil treated fruits showed minimum severity of fruil rot. Post-inoculation treatment ofneem oil was quite effective in reducing theA/temaria andAspergillus fruit rots. Pre or post-inoculation treatments ofleaf extracts of Azadirachta indica and Ocimum sanctum provided effective control ofbothA/ternaria andAspergillu.s rots ofberfruits.
Keywords: Zizyphus mauritiana; Altemaria alternata; Aspergillus 11ige; ber; fruit rots